A computer program for the analysis of bending of rectangular plates with or without opening and with various support conditions - Pugne, Jen Sandoval (1988)
This thesis is an effort to furnish a computer program for the analysis of plates by finite element method. The plates analyzed by this computer program are: a) bending of rectangular flat plates. b) Plates with or without opening which may vary in size and location but rectangular in shape. c) Plates with elastic supports at their corners, along their edges and /or over their entire area (elastic foundation). d) Plates with uniform load per unit area acting perpendicular to their surface, and/or uniform load (perpendicular or rotational) per unit length along their edges.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman.
Typescript.
Keywords: Plates (Engineering).; Finite element method